THE EFFECT OF GROSS DOMESTIC PRODUCT, INFLATION, DOMESTIC CREDIT TO PRIVATE SECTOR ON NET FOREIGN ASSETS ON INDONESIA’S BALANCE PAYMENT 1997-2018 - Nur Khotimah; Rheviani HK Putri; Lukman Yudho Prakoso; Sri Sundari; Agus Winarna; Yudi Sutrasna; Sri Murtiana; Juliana Juliana; Gabriel Choirul Alman; Supandi Supandi; Djamaludin Malik (Jurnal Cakrawala Ilmiah, 2022)
The slowdown in the world economy has impacted on several global commodity prices. As a result, this has resulted in an increasing current account deficit, in addition, Indonesia's balance of payments has fluctuated over the past decade. This study aims to determine the effect of gross domestic product, as well as the function of Bank Indonesia in maintaining the value of the rupiah to remain stable. The data used in this study is secondary data from 1997 to 2018. The analytical technique used in this study is multiple regression with Ordinary Least Square (OLS). The results of the study show that gross domestic product, inflation, and private sector domestic credit have a significant effect on foreign assets (NFA) simultaneously. Gross domestic product has a significant positive effect on NFA, and inflation and domestic credit to the private sector have a significant and negative effect on individual NFA. This research model shows that monetary policy is needed to maintain the balance of payments